KETERBUKAAN TANAH HUTAN BERSIFAT SEMENTARA DAN PERMANEN AKIBAT KEGIATAN PEMANENAN KAYU DI HUTAN ALAM PRODUKSI: Ajun Junaedi, Moh. Rizal dan Maria Chrissella Malango - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTOpenness of forest land due to timber harvesting is a loss of forest soil surface protection caused by logging,skidding, making forest road network, timber stockpiling, base camp and so forth. The aim of this research is tocalculate the percentage of forest land clearing due to temporary timber harvesting (tree felling, skidding, skid trailconstruction, TPn) and permanent nature (making of main and branch road network). The research was conducted atIUPHHK-HA PT Indexim Utama Central Kalimantan. The results show that the percentage of forest land clearing dueto timber harvesting is much higher (19.54%) than that of permanent (4.55%). Deforestation and main road makingactivities contributed the most to the percentage of temporary and permanent land clearing respectively by 10.66%and 3.94%.Keywords: Temporary and permanent, natural forest, forest land clearance, timber harvesting.